LAND DEBT IN THE LEGISLATION AND PRACTICE OF THE REPUBLIC OF SLOVENIA - Vujović, Dragana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
In 2003, the Republic of Slovenia adopted a new Real Law Code. One of the most significant innovations brought about by that code was the expansion of the numerus clausus of real subjective rights by introducing the institute of land debt, as a non-accessory lien, following the example of the German and Swiss institutes. The function of land debt is basically the same as the function of a mortgage, i.e. the provision of a specific claim or debt, with the main advantage over a mortgage, non-recourse. Since its introduction, land debt, in contrast to Germany, has been a less frequently used institution in business practice in Slovenia. In the last few years, before its abolition in 2013, the land debt came to the attention of the Slovenian public as an instrument that was almost exclusively used by suspects and accused persons in order to secure property in order to avoid paying debts. In the paper, we analyze the normative arrangement of this new institute, as well as the reasons for its abolition and deletion from the legal system of the Republic of Slovenia after ten years of existence.